ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN HUTANG PERUSAHAAN (Studi pada Perusahaan Sektor Consumer Goods yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Nimas Widanti; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2021)
The purpose of this research is to examine the factors that affect debt policy. There are eight factors in this research such as managerial ownership, institutional ownership, assets structure, firm size, profitability, free cash flow, business risk, and gross profit margin.The population of this research used all Consumer Goods companies in the Indonesian Stock Exchange in 2015-2019. This research using the purposive sampling method with a total sample of 225. The analysis method in this research uses multiple linear regression.The empirical result of this research shows that managerial ownership, profitability, and gross profit margin have a negative significant effect on debt policy. Assets structure and firm size have a positive significant effect on debt policy. While institutional ownership, free cash flow, and business risk do not have any effect on debt policy.